Reduce mean time to repair of mining equipment with lean six sigma - Hia, Selamat W.; Pramudjito, Prasetyo Adji Dian (Operations Excellence: Journal of Applied Industrial Engineering, 2024)
As the size and complexity of mining equipment grow, the impact of equipment failure becomes increasingly critical, often leading to costly downtime and production delays. Mining equipment performance depends on several factors, including equipment reliability, the operating environment, maintenance efficiency, operating processes, and the technical expertise of the personnel. Improving equipment reliability is essential to address these challenges, and one effective approach is to reduce the mean time to repair (MTTR), which significantly affects equipment availability. This study presents a case study on reducing the MTTR of the starter motor for coal mining equipment using the Lean Six Sigma method. Lean Six Sigma combines the principles of lean manufacturing and Six Sigma to identify inefficiencies and reduce variability. The findings reveal a substantial reduction in MTTR from 110 minutes to 10 minutes. Statistical analysis using a two-sample t-test confirms the significance of the improvement, with the process capability index (cpk) increasing from -2.94 to 6.96. This case study demonstrates the potential of Lean Six Sigma to address critical maintenance challenges, improve operational efficiency, and enhance equipment reliability in the mining sector.